User interface design of context-input-process-product evaluation application based on weighted product - Divayana, Dewa Gede Hendra; Adiarta, Agus; Santiyadnya, Nyoman; Suyasa, P. Wayan Arta; Andayani, Made Susi Lissia; Wiradika, I Nyoman Indhi; Wiguna, I Kadek Arta (Institute of Advanced Engineering and Science, 2024)
This study aimed to show the user interface design form of the context-input-process-product (CIPP) evaluation application based on weighted product as a measuring tool for the effectiveness level of blended learning in health colleges. This research approach was development research. The development model used was Borg and Gall. It focused on the design stage, initial trials, and revisions. The initial test of the user interface design involved 32 respondents. The tool for conducting it was in the form of a questionnaire, which contains 16 questions. The research was at the health colleges in Buleleng Regency. The data analysis technique of the initial test results was quantitative descriptive. It compared the percentage level of user interface design quality from the weighted product-based CIPP evaluation application with a quality standard which referred to a five scale. The results of this study indicated that the quality of the user interface design was relatively good. The research result’s impact on educational evaluation was new knowledge for pedagogic evaluators in maximizing the development of digital-based evaluation tools by integrating the decision support system method (weighted product) with the educational evaluation model (CIPP model).